EPOCHS. IV. SED Modeling Assumptions and Their Impact on the Stellar Mass Function at 6.5 ≤ z ≤ 13.5 Using PEARLS and Public JWST Observations - Thomas Harvey; Christopher J. Conselice; Nathan J. Adams; Duncan Austin; Ignas Juodžbalis; James Trussler; Qiong Li; Katherine Ormerod; Leonardo Ferreira; Christopher C. Lovell; Qiao Duan; Lewi Westcott; et al. (The Astrophysical Journal)
We utilize deep JWST Near Infrared Camera (NIRCam) observations for the first direct constraints on the Galaxy Stellar Mass Function (GSMF) at z > 10. Our EPOCHS v1 sample includes 1120 galaxy candidates at 6.5 < z < 13.5 taken from a consistent reduction and analysis of publicly available deep JWST NIRCam data covering the Prime Extragalactic Areas for Reionization Science, CEERS, GLASS, JADES GOOD-S, NGDEEP, and SMACS0723 surveys, totaling 187 arcmin ^2 . We investigate the impact of spectral energy distribution fitting methods, assumed star formation histories (SFHs), dust laws, and priors on galaxy masses and the resultant GSMF. While our fiducial GSMF agrees with the literature at z < 13.5, we find that the assumed SFH model has a large impact on the GSMF and stellar mass density (SMD), finding a 0.75 dex increase in the SMD at z = 10.5 between a flexible nonparametric and standard parametric SFH. Overall, we find a flatter SMD evolution at z ≥ 9 than some studies predict, suggesting a rapid buildup of stellar mass in the early Universe. We find no incompatibility between our results and those of standard cosmological models, as suggested previously, although the most massive galaxies may require a high star formation efficiency. We find that the “little red dot” galaxies dominate the z = 7 GSMF at high masses, necessitating a better understanding of the relative contributions of active galactic nucleus and stellar emission. We show that assuming a theoretically motivated top-heavy initial mass function (IMF) reduces stellar mass by 0.5 dex without affecting fit quality, but our results remain consistent with existing cosmological models with a standard IMF.